Religious Attitudes of Health Centers Clients and Social Capital: Examining the Relationships and Contributing Factors - Hamed Rezakhani moghaddam; Tohid Babazadeh; Fatemeh Joobjar; Zeinab Aghazadeh; Saeideh Aletaha; Aghil Habibi (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objective: The related literature shows that religious attitude has noticeable effects on all aspects of human life. This study was designed to examine the status of religious attitudes of clients attending health centers and its relationship with social capital. Method: This descriptive-analytical study was conducted on 160 clients of health centers in Kouchesfahan in 2014. To collect the required data, a standard 40-item questionnaire of religious attitudes and the 36-item Bullen's questionnaire concerning social capital were used. Then, correlation test, chi- square, t- test and ANOVA were employed to analyze the data. In this study, All the ethical issues were observed. Moreover, the authors did not report conflict of interest. Results: The results demonstrated that total means score for religious attitudes was calculated 125.9 ± 28.7. Minimum and maximum means were measured for "religious belief" and "religious behavior" dimension; they were 45.3 ± 11 and 37.6 ± 11.3, respectively. Furthermore, no significant relationship between social capital and dimensions of religious attitudes was found. Conclusion: According to the findings, it is safe to conclude that the more the religious behavior, the more favorable the social capital will be. Thus, promoting religious rites and practices in society can help to improve social capital. For downloading the full-text of this article please click here.